Desenho, produção e caracterização de proteína multiepitópica recombinante para a produção de soro anti-Micrurus corallinus - Gladstony de Oliveira Souza (2023)
A part of Brazilian snakebites are caused by coral snakes and the specific treatment against it is the use of Antielapidic antivenom (SAEL), produced against the venom of the species M. corallinus and M. frontalis. The availability of M. corallinus venom is low, which impacts directly the SAEL production chain in Brazil. This work aims to design, produce and validate a recombinant Multi- Epitopic Protein (PMEr-cor) as an alternative immunogen to replace, at least in part, M. corallinus venom in the production of SAEL. To achieve this goal, a sequence composed of previously validated epitopes, including new epitopic sequences mapped in silico of the main toxins of M. corallinus venom (Three- digit toxins and Phospholipases of type A2), was constructed. The gene encoding this immunogen was cloned and transformed into E. coli BL21DE3. PMEr-cor was expressed, purified, immunochemically characterized and used to immunize rabbits. A group of animals was inoculated with PMER-cor to characterize its immunogenic potential; another group was immunized with PMER-cor replacing M. corallinus venom, added to M. frontalis venom; and in the third group, the crude venom of the two species were administered, simulating the production of SAEL. As a result, PMER-cor was proven immunogenic, yet without inducing protection against the crude Micrurus sp venoms when used alone. The characterization of the antibodies produced against PMEr-cor together with M. frontalis venom demonstrated better preliminary performance in neutralization assays of the in vitro and in vivo venom's action. Although PMER-cor has notproven to be effective as a substitute immunogen for M. corallinus venom, after improving the composition of epitopes and spacers used, it could contribute to the biotechnological update of the SAEL production chain.